Empathic Behavior in Early Childhood under Condition of Taking the Mom’s Role in the Play - Yudina T.O., (Психолого-педагогические исследования, 2019)
Following the modern theoretical and empirical data on the problem of relation between the role-taking and empathy abilities we supposed that empathic behavior in early childhood could be realized through acquiring the role “mom” within the role playing. In order to test our suppose we have conducted the ingroup experiment with 36 toddlers (M=35 months) and compared the frequency of the empathic behavior under two conditions: 1) taking the role of mom and 2) taking the role of friend by the toddler withing the experimental story-play with toys. According to our hypothesis we expected that children would display the empathic behavior more frequent in the condition of taking the mom’s role. Our hypothesis was not confirmed since the difference between conditions has been not significant. Such results reveal that the parental models do not serve significant mediating role in the child’s learning of prosocial behavior.